Brain and cerebellar hemidysplasia in a case with ipsilateral body dysplasia and suspicion of CHILD syndrome - Schmidt-Sidor, Bogna; Obersztyn, Ewa; Szymańska, Krystyna; Wychowski, Jan; Mierzewska, Hanna; Wierzba-Bobrowicz, Teresa; Stępień, Tomasz (Folia Neuropathologica, 2008)
CHILD syndrome is an acronym for Congenital Hemidysplasia with Ichthyosiform nevus and Limb Defects. This is an X-linked dominant disorder affecting females with early lethality in hemizygous males. The clinical features are congenital hemidysplasia with ichthyosiform erythroderma and ipsilateral hypoplasia of limbs and other parts of the skeleton as well as defects of the brain, heart, kidney and lung. CHILD syndrome is caused by mutations in the NSDHL (steroid dehydrogenase-like protein) gene at Xq28, which affects cholesterol biosynthesis. A female premature newborn with left side body hemidysplasia and ipsilateral defects of the skin, visceral organs and brain is reported. Analysis of child DNA isolated from skin fibroblasts showed missense mutation c.1046A>G;PpY349C in the NSDHL gene that could cause the phenotype.